2013
DOI: 10.5194/nhess-13-2797-2013
|View full text |Cite
|
Sign up to set email alerts
|

Cold fronts in the Colombian Caribbean Sea and their relationship to extreme wave events

Abstract: Abstract. Extreme ocean waves in the Caribbean

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 17 publications
(17 reference statements)
1
28
0
2
Order By: Relevance
“…The results show historical events with large energetic content, representing storm propagation towards the coast. The bars are consistent with the meteomarine conditions during winter due to the strong winds and related to the trade winds and Cold Fronts passage on the study zone [6,7] The values of the month of July indicate low pressure events related to the hurricane seasons, with 300 events greater than 1. It is shown in Figure 12 the wave height rose calculated energetically by storm with the application AppMar 1.0 © .…”
Section: Figure 8 Mean and Maximum Monthly Number Of Stormssupporting
confidence: 71%
“…The results show historical events with large energetic content, representing storm propagation towards the coast. The bars are consistent with the meteomarine conditions during winter due to the strong winds and related to the trade winds and Cold Fronts passage on the study zone [6,7] The values of the month of July indicate low pressure events related to the hurricane seasons, with 300 events greater than 1. It is shown in Figure 12 the wave height rose calculated energetically by storm with the application AppMar 1.0 © .…”
Section: Figure 8 Mean and Maximum Monthly Number Of Stormssupporting
confidence: 71%
“…Conversely, the dry season of the year (from December to May) is influenced by the increase of trade winds from the northeast (Bernal et al, 2006;Paramo et al, 2011) and the passage of cold fronts coming from the Northern Hemisphere, an event which produces strong tides (Ortiz et al, 2013). Extreme wave heights covering return periods of 5 and 10 years show significant heights which oscillate between 3 and 4.2 m. Meanwhile, the extreme waves for return periods of 25, 50, and 100 years take significant height values which vary between 3.6 and 4.8 m.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The rising hot air cools down, producing clouds, storms, strong winds, and the pressure gradient in the area. Furthermore, it increases the wave height or swell through its passage along the Colombian Caribbean coast (Ortiz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have only been a few previous climatological studies of the relationship between atmospheric conditions and H s values: Ortiz‐Royero et al . [] associated extreme wave events in the Caribbean Sea with cold frontal events; Pingree‐Shippee et al . [] investigated a few case studies of storms and extremes wave heights in the Bering and Chukchi Sea and found stationary storms produce the largest, steepest waves.…”
Section: Introductionmentioning
confidence: 99%